Secrets, sorrow and the feminine subjective: Nüshu references in the work of contemporary Chinese artist Ma Yanling. (1st March 2015) - Guest, Luise
This is an investigation into the significance of the ancient 'secret' women's phonetic syllabary, Nüshu, in the performance and painting work of contemporary artist Ma Yanling, based on two extensive interviews with the artist in October and November 2013 and a close analysis of specific works. This article examines, first, the ways in which the gendered communication of life-stories and the exploration of female grievance found in Nüshu texts (the supposedly 'secret' women's phonetic syllabary used by peasant women in Jiangyong County, Hunan Province until the late 1980s) continues to have relevance in the work of a contemporary artist. It is argued that Nüshu texts (intended to be chanted aloud) are in themselves performative and cathartic in a similar manner to contemporary performance art practices. Second, the article argues that the ways in which Ma Yanling's work subverts the iconography of Mao-era propaganda portraiture and its Pop-inspired satire in contemporary Chinese art (Zhongguo Dangdai Yishu) represent complex and contradictory aspects of female experience and feminine subjectivity in today's China.